PERBANDINGAN USER EXPERIENCE APLIKASI DOMPET DIGITAL PADA MAHASISWA MENGGUNAKAN METODE UEQ (USER EXPERIENCE QUESTIONNAIRE) - Susanti, Midesi; Wahyuni, Asri (LPPM Universitas Bina Bangsa, 2024)
The popularity of digital payments using electronic money is increasing in Indonesia along with the growth of the financial technology (fintech) industry. Currently, the fastest growing and most widely used digital wallet applications in Indonesia are Dana, Ovo, and Go-Pay. The purpose of this study was to determine the user experience of Dana, Ovo, and Go-pay digital wallets using the User Experience Questionnaire (UEQ) and the SPPS 25 analysis tool. This study uses a quantitative method, the sample in this study was 100 students who used digital wallets who were selected by purposive sampling. The data collection instrument used the UEQ questionnaire consisting of 26 questions grouped into 6 measurement scales. The results of the study showed that the three applications received positive UEQ scores on all measurement scales. The Go-pay application received the highest score on the Efficiency and Dependability scales. While the highest scores for the Ovo and Dana applications were on the Attractiveness and Perpicuity scales, respectively. In general, the user experience of the three applications is considered good, but there are still several aspects that need to be improved, such as the appearance of the interface, the smoothness of the transaction process, and supporting features